2016
DOI: 10.1177/0141076816643324
|View full text |Cite
|
Sign up to set email alerts
|

Do invitations for cervical screening provide sufficient information to enable informed choice? A cross-sectional study of invitations for publicly funded cervical screening

Abstract: SummaryObjective: To investigate whether invitations for publicly funded cervical screening provide sufficient information to enable an informed choice about participation. Design: Cross-sectional study using a checklist of 23 information items on benefits and harms from cervical screening and the risks related to cervical cancer. Material: Invitations to publicly funded cervical screening in 10 Scandinavian and English-speaking countries. Setting: Ten Scandinavian and English speaking countries. Participants:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 26 publications
(31 reference statements)
1
20
0
Order By: Relevance
“…As women highly favored receiving expanded information and the source to be a qualified public health authority, invitation letters sent by the NCCSP could serve that purpose. A previous study found that Norwegian invitation letters included none of suggested information items on harms and benefits of CC screening and CC-related risks (Kolthoff et al, 2016). Our findings suggest that the provision of additional information on harms is unlikely to result in substantial reductions in screening participation and supports the proposition to expand the letters.…”
Section: Policy Implicationssupporting
confidence: 65%
See 2 more Smart Citations
“…As women highly favored receiving expanded information and the source to be a qualified public health authority, invitation letters sent by the NCCSP could serve that purpose. A previous study found that Norwegian invitation letters included none of suggested information items on harms and benefits of CC screening and CC-related risks (Kolthoff et al, 2016). Our findings suggest that the provision of additional information on harms is unlikely to result in substantial reductions in screening participation and supports the proposition to expand the letters.…”
Section: Policy Implicationssupporting
confidence: 65%
“…For the NCCSP, invitation letters may be an effective way of increasing participation (Camilloni et al, 2013;Everett et al, 2011), but must provide a balance between encouraging screening and ensuring that women make informed choices based on unbiased information about harms and benefits (Irwig et al, 2006). A study has found that invitation letters in 10 developed countries were biased in favor of participation by omitting important information on harms, for instance overdiagnosis and overtreatment (Kolthoff et al, 2016). Failing to provide such information reduces women's ability to make an informed choice (Kolthoff et al, 2016;Hersch et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used an established checklist of information items about cervical screening,30 building on earlier evaluations of breast cancer screening communications 25 31 32. We assessed quantitative presentation formats considering the recommendations listed in table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Most information material is non-numerical. [11] This may be justified, since previous research indicates that people can have difficulty deriving meaning from numerical risk communication. [12,13] However, we need to study how different types of information affect patients.…”
mentioning
confidence: 99%